Measurement of radioactive contamination in the CCD's of the DAMIC experiment. Issue 4 (May 2016) - Aguilar-Arevalo, A; Amidei, D; Bertou, X; Bole, D; Butner, M; Cancelo, G; Castañeda Vásquez, A; Chavarria, A E; de Mello Neto, J R T; Dixon, S; D'Olivo, J C; Estrada, J; et al.
Abstract: DAMIC (Dark Matter in CCDs) is an experiment searching for dark matter particles employing fully-depleted charge-coupled devices. Using the bulk silicon which composes the detector as target, we expect to observe coherent WIMP-nucleus elastic scattering. Although located in the SNOLAB laboratory, 2 km below the surface, the CCDs are not completely free of radioactive contamination, in particular coming from radon daughters or from the detector itself. We present novel techniques for the measurement of the radioactive contamination in the bulk silicon and on the surface of DAMIC CCDs. Limits on the Uranium and Thorium contamination as well as on the cosmogenic isotope 32 Si, intrinsically present on the detector, were performed. We have obtained upper limits on the 238 TJ ( 232 Th) decay rate of 5 (15) kg _1 d _1 at 95% CL. Pairs of spatially correlated electron tracks expected from 32 Si- 32 P and 210 Pb- 210 Bi beta decays were also measured. We have found a decay rate of 80+ l10 -65 kg _1 d _1 for 32 Si and an upper limit of - 35 kg- 1 d -1 for 210 Pb, both at 95% CL.